Changing the game but keeping to the rules - Beatriz Blanco (Eludamos)
The vulnerabilities faced by social minorities in Brazil, such as women, Black people, and LGBTQ+ people, are also very prevalent in local gaming cultures. Because of this, members of these groups organize collectives through social media to debate strategies and to provide mutual support for their esports initiatives. In the last few years, many of these activist collectives were absorbed by formal esports organizations, with some of their members now leading equality and diversity initiatives for esports in Brazil. Nevertheless, the movement from grassroots activists to PR representatives has contradictions, especially considering how social media platforms mediate the transition between activism and cause marketing. This paper aims to highlight some of these ambivalences, and how they impact the most vulnerable esports workers in Brazil.